A concisely automated synthesis of TSPO radiotracer [18F]FDPA based on spirocyclic iodonium ylide method and validation for human use. (20th January 2020) - Wang, Lu; Yao, Shaobo; Tang, Ruikun; Zhu, Honghao; Zhang, Lingling; Gong, Jian; Chen, Qiusong; Collier, Thomas Lee; Xu, Hao; Liang, Steven H.
Abstract : Fluorine‐18 labeled N, N ‐diethyl‐2‐(2‐(4‐(2‐fluoroethoxy)phenyl)‐5, 7‐dimethylpyrazolo[1, 5‐ a ]pyrimidin‐3‐yl)acetamide ([ 18 F]FDPA) is a potent and selective radiotracer for positron‐emission tomography (PET) imaging of the translocator protein 18 kDa (TSPO). Our previous in vitro and in vivo evaluations have proven that this tracer is promising for further human translation. Our study addresses the need to streamline the automatic synthesis of this radiotracer to make it more accessible for widespread clinical evaluation and application. Here, we successfully demonstrate a one‐step radiolabeling of [ 18 F]FDPA based on a novel spirocyclic iodonium ylide (SCIDY) precursor using tetra‐ n ‐butyl ammonium methanesulfonate (TBAOMs), which has demonstrated the highest radiochemical yields and molar activity from readily available [ 18 F]fluoride ion. The nucleophilic radiofluorination was completed on a GE TRACERlab FX2 N synthesis module, and the formulated [ 18 F]FDPA was obtained in nondecay corrected (n.d.c) radiochemical yields of 15.6 ± 4.2%, with molar activities of 529.2 ± 22.5 GBq/μmol (14.3 ± 0.6 Ci/μmol) at the end of synthesis (60 minutes, n = 3) and validated for human use. This methodology facilitates efficient synthesis of [ 18 F]FDPA in a commercially available synthesis module, which would be broadly applicable for routine production and widespread clinical PET imaging studies. Abstract : The present study reports a successful one‐step radiolabeling of fluorine‐18 labeled N, N ‐diethyl‐2‐(2‐(4‐(2‐fluoroethoxy)phenyl)‐5, 7‐dimethylpyrazolo[1, 5‐ a ]pyrimidin‐3‐yl)acetamide ([ 18 F]FDPA) on a GE TRACERlab FX2 N synthesis module with a novel spirocyclic iodonium ylide (SCIDY) precursor, which has demonstrated the highest radiochemical yields and molar activity from [ 18 F]fluoride ion. This protocol has been validated for human use.